Near‐Infrared‐Emitting Boron‐Difluoride‐Curcuminoid‐Based Polymers Exhibiting Thermally Activated Delayed Fluorescence as Biological Imaging Probes. (12th July 2021) - Paisley, Nathan R.; Halldorson, Sarah V.; Tran, Michael V.; Gupta, Rupsa; Kamal, Saeid; Algar, W. Russ; Hudson, Zachary M.
Abstract: Near‐infrared‐emitting polymers were prepared using four boron‐difluoride‐curcuminoid‐based monomers using ring‐opening metathesis polymerization (ROMP). Well‐defined polymers with molecular weights of ≈20 kDa and dispersities <1.07 were produced and exhibited near‐infrared (NIR) emission in solution and in the solid state with photoluminescence quantum yields (ΦPL ) as high as 0.72 and 0.18, respectively. Time‐resolved emission spectroscopy revealed thermally activated delayed fluorescence (TADF) in polymers containing highly planar dopants, whereas room‐temperature phosphorescence dominated with twisted species. Density functional theory demonstrated that rotation about the donor–acceptor linker can give rise to TADF, even where none would be expected based on calculations using ground‐state geometries. Incorporation of TADF‐active materials into water‐soluble polymer dots (Pdots) gave NIR‐emissive nanoparticles, and conjugation of these Pdots with antibodies enabled immunofluorescent labeling of SK‐BR3 human breast‐cancer cells. Abstract : Polymers exhibiting near‐infrared thermally activated delayed fluorescence (TADF) or room‐temperature phosphorescence are prepared from four boron‐difluoride‐curcuminoid‐based monomers. Incorporation of TADF‐active materials into water‐soluble polymer dots (Pdots) and subsequent antibody conjugation enabled near‐infrared immunofluorescent labeling of SK‐BR3 human breast‐cancer cells.